Sulfated levan from Halomonas smyrnensis as a bioactive, heparin-mimetic glycan for cardiac tissue engineering applications - TOKSOY ÖNER, EBRU; EROĞLU, MEHMET SAYIP (ELSEVIER SCI LTD, 2016)
Chemical derivatives of levan from Halomonas smyrnensis AAD6T with low, medium and high levels of sulfation were synthesized and characterized by FTIR and 2D-NMR. Sulfated levan samples were found to exhibit anticoagulation activity via the intrinsic pathway like heparin in a dose-dependent manner. Exceptionally high heparin equivalent activity of levan sulfate was shown to proceed via thrombin inhibition where decreased Factor Xa activity with increasing concentration was observed in antithrombin tests and above a certain concentration, levan sulfate showed a better inhibitor activity than heparin. In vitro experimental results were then verified in silico by docking studies using equilibrium structures obtained by molecular dynamic simulations and results suggested a sulfation dependent binding mechanism. With its high biocompatibility and heparin mimetic activity, levan sulfate can be considered as a suitable functional biomaterial to design biologically active, functionalized, thin films and engineered smart scaffolds for cardiac tissue engineering applications. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Levan; Halomonas smyrnensis; Sulfation; Heparin mimetics; Anticoagulant activity; ANTICOAGULANT ACTIVITY; ANTIOXIDANT ACTIVITIES; POLYSACCHARIDE; BIOMATERIALS; FILMS; SULFONATION; COMPLEX